{2′-[1-(5-Bromo-2-oxidophenyl)ethylidene]-benzohydrazidato(2-)} tris(pyridine)nickel(II) pyridine solvate - Ali, Hapipah Mohd; Yamin, B.M.; Khamis, N.A. (International Union of Crystallography, 2004)
In the title compound, [Ni(C15H10BrClN 2O2)(C5H5N) 3]·-C5H5N, the Ni atom is coordinated by three pyridine molecules and one oxygen-containing ligand in a tridentate manner via O, N and O atoms. The geometry of the Ni atom is distorted octahedral. There are no significant intermolecular interactions in the crystal structure. © 2004 International Union of Crystallography Printed in Great Britain - all rights reserved.